Systemic treatment of psoriasis: from methotrexate to biologics - Olga Yu. Olisova; Ekaterina M. Anpilogova (State Scientific Center of Dermatovenereology and Cosmetology, 2020)
Psoriasis is one of the most frequent chronic inflammatory skin diseases and it has been of interest to many scientists for ages. The review presents data on all systemic treatment options, that are to date officially registered in Russian Federation for moderate-to-severe psoriasis. Aspects of the mechanism of action, efficacy and tolerability of both basic drugs (methotrexate, cyclosporine, acitretin) and biologics (infliximab, adalimumab, etanercept, certolizumab pegol, ustekinumab, guselkumab, secukinumab, ixekizumab, netakimab) and small molecules (tofacitinib, apremilast) are considered in detail. Special emphasis is placed on the important nuances of biological therapy: immunogenicity, drugs' survival and switch due to lack of efficacy. Invention of biologics signified a new era of moderate-to-severe psoriasis treatment. It became possible to achieve complete clinical remission more safely, which significantly improved the quality of life of patients. However, due to the unknown etiology of psoriasis, there is still no universal remedy that would allow to cure every patient, this fact makes scientists from all over the world keep conducting numerous clinical trials to find even more effective and safe therapeutic options.